Hubungan Emotional Attachment dengan Celebrity Worship pada Dewasa Awal Penggemar NCT (Neo Culture Technology) - Dara Citra Malasya Fitri; Bayu Sekar Larasati (Indonesian Journal Publisher, 2023)
Celebrity worship is a parasocial relationship in which individuals are obsessed with their favorite idols. The study aimed to determine the relationship between emotional attachment and celebrity worship in early adult NCT (Neo Culture Technology) fans. The subjects in this study were 280 early adult NCT fans aged 18-25 years. The technique for collecting data for this research uses a Likert scale, namely the Emotional Attachment Scale and the Celebrity worship Scale. The reliability coefficient for the Emotional Attachment scale is α = 0.874, while the reliability coefficient for the Celebrity worship scale is α = 0.842. Because the data has an abnormal distribution, the data analysis technique uses the Spearman's Rho correlation technique. The results showed a correlation coefficient of 0.717 and a significance value of p = 0.000 (p>0.01). This indicates a positive relationship between emotional attachment and celebrity worship among NCT fans in early adulthood.